Degradation of Ciprofloxacin Antibiotic Waste Using TiO2 Nanotube with Addition of Anthocyanin Dye-Sensitizer In Photocatalysis Process: Review - Fidarohman, Fidarohman; Putri, Berliana Tristati; Putri, Martina Reza; Kustiningsih, Indar; Slamet, Slamet (Jurnal Rekayasa Kimia & Lingkungan, 2023)
An antibiotic-containing waste entering the water bodies is very dangerous because it can disturb the balance of the ecosystem and can modify the genetic information of natural bacteria so that resistance occurs. One type of antibiotic is ciprofloxacin (CIP) which can pollute aquatic ecosystems. One potential method that can be used to degrade the CIP is photocatalysis since it is low cost, highly effective, and environmentally friendly. To improve the performance of TiO photocatalyst, morphological engineering is carried out to form TiO nanotube arrays and then coated with natural anthocyanin sensitizer. The morphological engineering of TiO can be done through the anodization process. It is an electrochemical coating process that can convert metals to porous metal oxide layers. The effectiveness of the TiO2 photocatalyst in degrading pollutants can be increased by a dye-sensitizer addition. Commonly, natural anthocyanin dyes are chosen as sensitizers on the TiO2 semiconductor surfaces. Visible light is absorbed by the dye-sensitizer substances to speed up the electron excitation mechanism. The dye-sensitizer addition causes the TiO2 photocatalyst to be more responsive to visible light. The addition of the dye-sensitizer on the surface of TiO2 nanotubes has the potential to increase the degradation of ciprofloxacin waste using a photocatalytic process.